2017
DOI: 10.1097/iae.0000000000001417
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Parafoveal Capillary Nonperfusion and Macular Function in Eyes With Branch Retinal Vein Occlusion

Abstract: Optical coherence tomography angiography visualized parafoveal capillary nonperfusion in superficial and deep layers individually in eyes with resolved branch retinal vein occlusion. Retinal sensitivity was significantly reduced at these capillary nonperfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Manabe et al reported the association between parafoveal capillary nonperfusion and retinal sensitivity in eyes with resolved BVO patients. They concluded mean retinal sensitivity at the capillary non-perfusion area was significantly lower than that at the capillary perfusion area [20]. It would be of interest that whether retinal sensitivity measurement is also useful in such cases; however, the purpose of the current study was to investigate the usefulness of measuring retinal sensitivity in eyes with BVO and ME, and it was beyond the purpose of the current study.…”
Section: Discussionmentioning
confidence: 89%
“…Manabe et al reported the association between parafoveal capillary nonperfusion and retinal sensitivity in eyes with resolved BVO patients. They concluded mean retinal sensitivity at the capillary non-perfusion area was significantly lower than that at the capillary perfusion area [20]. It would be of interest that whether retinal sensitivity measurement is also useful in such cases; however, the purpose of the current study was to investigate the usefulness of measuring retinal sensitivity in eyes with BVO and ME, and it was beyond the purpose of the current study.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have shown the clinical relevance of vessel density measurements in predicting clinical disease in RVO. 3,[7][8][9][10][11][12][13] In disease processes such as RVO, it is important to accurately measure this quantitative metric as it would be an ideal way to monitor the ischemic index over time. Accurately measuring the averaged VLD or PD or difference with treatment and time could provide clinicians a secondary measure to monitor for improvement, stability or worsening of macular ischemia, which is directly correlated with, and may perhaps precede and be predictive of BCVA.…”
Section: Discussionmentioning
confidence: 99%
“…OCTA has demonstrated that quantitative metrics including foveal avascular zone (FAZ) enlargement [3][4][5][6] and parafoveal capillary nonperfusion measured by vessel density (VD) are correlated with best corrected visual acuity (BCVA). 3,[7][8][9][10][11][12][13] Even with these advancements, fluorescein angiography (FA) still remains a common method to image retinal non-perfusion and neovascularization in RVO, although with significant limitations. These include the need for invasive intravenous dye injection, which can rarely induce an allergic reaction with anaphylaxis, 14 the loss of retinal vascular detail due to dye leakage and pooling, as well as the inability to evaluate the depth and extent of disease within the various retinal plexuses.…”
Section: Introductionmentioning
confidence: 99%
“…Retinal nerve fiber and ganglion cells are located within a uniform and arcuate pathway and do not cross each other’s path [ 30 , 31 ]. In contrast, the retinal vascular pathway does not arcuate uniformly; a major branch retinal vein may appear arcuate, but secondary and tertiary branches and capillaries develop into a network rather than an arc [ 32 , 33 ]. Manabe et al reported parafoveal capillary nonperfusion frequently in patients with completely resolved branch RVO (25 of 27 eyes, 92.6%) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%